Evaluation of Characteristics :Case Study of the Implemented Speed Humps in the City of Misurata (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Speed humps are one of the traffic calming methods that fall under the speed limit. In many countries, such devices have been the subject of careful investigations (to assess their effectiveness and disadvantages), and this has resulted in several modifications in their design to improve their performance. On the contrary, no systematic and scientific studies have been carried out on Libyan installations. This study aims to examine and classify the implemented speed humps in the city of Misurata and compare them with international standards. The sample for this study consists of 62 bumps installed in the city of Misurata. Based on the results obtained from the sample and according to the Institute of Transportation Engineers ITE standards, it was found that 13% can be classified as short type (speed bump), 21% are smooth type (speed hump), and 66% are out of specification. It was also found that 34% of the sample did not include a warning sign in front. Statistical analysis was carried out to evaluate the distance between the bump and the intersection and the distance between the bump and the warning sign, and it was found that the range between the largest values and the smallest values is very large for both distances, which indicates randomness in implementation and a lack of specific specifications.